2022
DOI: 10.26434/chemrxiv-2022-1sq2c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperativity between sodium ions and water molecules facilitates lipid mobility in model cell membranes

Abstract: Cellular membranes are surrounded by an aqueous buffer solution containing various ions, which influence the hydration layer of the lipid head groups. At the same time, water molecules hydrating the lipids play a major role in facilitating the organisation and dynamics of membrane lipids. Employing fluorescence microscopy imaging and fluorescence recovery after photobleaching measurements, we demonstrate that the cooperativity between water and sodium (Na+) ions is crucial to maintain lipid mobility upon the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…One way of describing membrane dehydration would be to define a state where the amount of hydrating water decreases to a level where the dynamic or structural properties of the membrane begin to be affected. Based on the experiments reported here as well as our recent works, 37,50,51 both the dynamics and the structure of the membrane are gradually affected when the first hydration shell of the lipids is perturbed. In the case of the zwitterionic phosphocholine lipids, this happens when the hydration drops below about 12 molecules per lipid.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…One way of describing membrane dehydration would be to define a state where the amount of hydrating water decreases to a level where the dynamic or structural properties of the membrane begin to be affected. Based on the experiments reported here as well as our recent works, 37,50,51 both the dynamics and the structure of the membrane are gradually affected when the first hydration shell of the lipids is perturbed. In the case of the zwitterionic phosphocholine lipids, this happens when the hydration drops below about 12 molecules per lipid.…”
Section: Discussionsupporting
confidence: 66%
“…The observed changes in lipid partitioning are associated with the decreased hydrophobic mismatch, but unlike the height mismatch data, they are also strongly dependent on the lipid mobility. Since lipid mobility decreases strongly with decreasing membrane hydration, 37,50,51 it is not too surprising that we do not see a steady increase in the partitioning of the L d phase lipids into the L o phase. At lower membrane hydration states, we observed a competition between the lower hydrophobic mismatch, which favours lipid admixing, and the lower diffusivity, which hinders mixing.…”
Section: Hydrophobic Mismatch and Line Tension Under Dehydration Cond...mentioning
confidence: 84%
See 1 more Smart Citation
“…At 50% RH and less, the mobility of lipids is almost completely ceased, which results from the breaking of the first hydration shell surrounding a single lipid head group moiety. Furthermore, other recent studies of ours showed that the dynamics of lipids under dehydration conditions is strongly affected by the ionic composition of the buffer hydrating the membrane 50 . Although lipids in the presence of Na + ions remain mobile in humidity above 50% RH, in MilliQ water upon dehydration to 85% RH their mobility is already significantly reduced.…”
Section: Nanoscale Structural Changes Under Dehydration Conditionssupporting
confidence: 49%